STATE CONSTITUTIONAL LEGAL REGULATIONS ON WAR AND NATIONAL DEFENSE IN THE INDONESIAN CONSTITUTION AND ITS IMPLICATIONS FOR NATIONAL SOVEREIGNTY - Tanjung, Indra Utama (PT. Sinergi Legal Publisher, 2025)
The regulation on war and national defense in the Indonesian constitutional law system has a strategic position in maintaining national sovereignty. The provisions in the 1945 Constitution of the Republic of Indonesia, especially Article 10, Article 11, and Article 30, provide a constitutional basis for the President as the holder of the highest power over the Armed Forces, with a checks and balances mechanism through the approval of the House of Representatives in making decisions to declare war. In addition, the universal people's defense and security system (Sishankamrata) emphasizes the participatory role of all citizens in maintaining the integrity of the nation and state. However, in a global era marked by non-conventional threats such as cyber warfare, disinformation, cross-border terrorism, and hybrid conflicts, the existing constitutional law regulations are considered not yet fully adaptive and responsive. This study uses normative legal research methods with a statutory, conceptual, and comparative approach. The research findings show that there are normative gaps in defining a “state of war” and decision-making mechanisms in dealing with non-conventional threats. In addition, the implementation of the principle of civilian supremacy over the military and the optimization of legislative oversight in defense policy still face various obstacles. The implications of the weaknesses in these regulations have the potential to hinder the effectiveness of protecting national sovereignty. Therefore, it is necessary to update the regulation of constitutional law in order to be able to respond to the dynamics of modern threats and ensure that national sovereignty is effectively protected within the framework of a democratic state of law.